BOOSTING TRUST AMONG STAKEHOLDERS: THE IMPACT OF GOVERNANCE ADJUSTMENTS AND ACCOUNTING CONSERVATISM IN PALESTINIAN BANKS - Awad , Mariam; Khoury, Sami (Ayden International Journal of Banking, Finance and Technology, 2024)
The Palestinian banking sector stands as a pivotal component within the Palestinian financial system, encompassing a roster of 15 operational banks. Of these, six are locally owned national banks, listed on the Palestinian stock market: Bank of Palestine, Al-Quds Bank, the National Bank, the Palestinian Investment Bank, the Arab Islamic Bank, and the Palestinian Islamic Bank. These institutions are governed by the Palestinian Monetary Authority, which articulates precise banking policies aimed at nurturing deposit growth and prudently investing shareholder and investor funds. While the historical origins of accounting conservatism have raised concerns about its potential impact on the quality of financial information, it has evolved into an essential requirement for financial statement users. The collapse of several prominent corporations underscored the importance of accounting conservatism in curbing opportunistic managerial practices, such as profit manipulation, extrabudgetary financing, and other transgressions against the principles of conservatism. The convergence of accounting conservatism and corporate governance functions as a mechanism to mitigate agency problems, improving the quality of financial reporting. Accounting conservatism assumes a pivotal role in curtailing profit manipulation and elevating the caliber of accounting information. Recent developments in accounting discourse spotlighted corporate governance, intensified scrutiny on profit manipulation practices, and emphasized the significance of appropriately tailored accounting information for capital markets.